HUBUNGAN PENGETAHUAN DAN MOTIVASI TERHADAP PEMENUHAN KEBUTUHAN DASAR PASIEN GANGGUAN JIWA DENGAN DEFISIT PERAWATAN DIRI - nauli, Fathra Annis; susanti, Rifi '; ', Wasisto utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract This study aimedtoidentify therelationship between knowledgeandmotivationtofulfillthe basicneeds ofmental patientswithself-care deficiti. This studi used descriptive methodusing cross-sectional correlation. The study was conductedinTampan Mental HospitalRiau Provinceon33 respondentswere takenusingtotal sampling method. Measuring instrument usedaquestionnairethathas beentested for validityandreliability.The analysis usedunivariateandbivariateanalysis usingChiSquaretest. The results showed thatthere was nocorrelationbetweenknowledgeof respondentsandself-caredeficitwith asignificance levelof 0.05was obtainedp>0.05 is0.923. For motivational factor, it was found that there was nosignificant relationshipbetween thelevelof motivationandthe level ofself-caredeficitwithsignificance levelof 0.05withp>0.05 is1.000. The results ofthis studyit was expected tonursing staffinhospitalsto improve the patient’s psychomotor abilitytoperform well self-care. Keywords : Knowledge, Motivation, Self-caredeficit